3(x+7)+6=27

Simple and best practice solution for 3(x+7)+6=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+7)+6=27 equation:



3(x+7)+6=27
We move all terms to the left:
3(x+7)+6-(27)=0
We add all the numbers together, and all the variables
3(x+7)-21=0
We multiply parentheses
3x+21-21=0
We add all the numbers together, and all the variables
3x=0
x=0/3
x=0

See similar equations:

| -10+5m=90 | | 83+4x+27=5x+2x+29 | | 8=3a-4 | | -5v+35=-3v+47 | | 7-5x=3-6x | | 6+34=-4(5x-10) | | 4x-15=7x-44 | | -9.8=j-17.2 | | 9x−5=4x+14.25 | | 9(6+x)=54 | | 3x-5(-2+3x)=-24x | | n/6=26 | | p+32=943 | | 12x+21=-39+36 | | 5x=|3x-8| | | x+25=4x-26 | | -32+3x=7 | | w-575=338 | | F×x=x×2+4x-21 | | 2x-6=3x=1-x-7 | | -6x=7x+13 | | 8x+10=35+3x8x+10=35+3x | | 7x−2=6x+6 | | 4x-2{x+3}=8 | | 10n-4=34 | | 24x-15x=7x+12x | | 1/6x=55/12 | | 9*19^x=11*8^x | | 3.1=x | | 3-x+8=2 | | 10d-17=53 | | 8x+40=-4x+-28 |

Equations solver categories